2022
DOI: 10.1212/wnl.0000000000200758
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Performance of Different Respiratory Test Parameters for Detection of Early Respiratory Insufficiency in Patients With ALS

Abstract: Objective:To compare the performance of different respiratory function testing in a multidisciplinary ALS clinic.Methods:Demographics, clinical data, and respiratory testing parameters were abstracted from the medical records of patients who attended a multidisciplinary ALS clinic from 2008-2016. We compared the performance of the three primary respiratory test parameters used by Medicare for the initiation of non-invasive ventilation (NIV), (forced vital capacity (FVC) < 50% predicted, maximum inspiratory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Measuring oxygen saturation by pulse oximetry (SpO 2 ) is widely available and practical for assessing oxygenation status in a clinic or the home. Use of nocturnal SpO 2 offers utility for early NIV qualification compared with FVC 35 . However, any desaturation in an individual with ALS with normal lung parenchyma, airways, and vasculature is most likely related to hypoventilation causing carbon dioxide retention.…”
Section: Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…Measuring oxygen saturation by pulse oximetry (SpO 2 ) is widely available and practical for assessing oxygenation status in a clinic or the home. Use of nocturnal SpO 2 offers utility for early NIV qualification compared with FVC 35 . However, any desaturation in an individual with ALS with normal lung parenchyma, airways, and vasculature is most likely related to hypoventilation causing carbon dioxide retention.…”
Section: Technologymentioning
confidence: 99%
“…Use of nocturnal SpO 2 offers utility for early NIV qualification compared with FVC. 35 However, any desaturation in an individual with ALS with normal lung parenchyma, airways, and vasculature is most likely related to hypoventilation causing carbon dioxide retention.…”
Section: Technologymentioning
confidence: 99%
“…In amyotrophic lateral sclerosis (ALS), MIP, MEP, and SNIP decline earlier than sitting FVC and may thus be useful in tracking early respiratory muscle function decline in ALS. [67][68][69][70] Static pressures can be measured in a clinic using the MicroRPM respiratory pressure meter (MD Spiro, Lewiston, ME). (Figure 7)…”
Section: Maximum Inspiratory and Expiratory Pressuresmentioning
confidence: 99%
“…Overnight pulse oximetry becomes abnormal earlier in ALS on average than FVC. 70 However, oximetry is only about 70% sensitive in detecting mild hypercapnia in the setting of respiratory muscle weakness and is not useful for detecting hypoventilation. [74][75][76] End-tidal and transcutaneous CO2 measuring devices are now widely available for noninvasive point-ofcare estimation of PaCO2 77 although neither measurement is reimbursed for outpatient use by health care insurers in the United States.…”
Section: Blood Gasesmentioning
confidence: 99%
“…Several respiratory tests and arterial blood gas analysis (ABGs) parameters have been evaluated, showing a different efficacy in the correct evaluation of initial respiratory dysfunction among ALS phenotypes ( Heiman-Patterson et al, 2018 ). In recent studies, maximum inspiratory pressure (MIP), overnight pulse oximetry (OvOx; Kelly et al, 2022 ), serum base excess (SBE), and carbonate (HCO3-; Manera et al, 2020 ) have been confirmed as the earliest predictors of respiratory dysfunction, being capable of detecting subtle muscle weakness and nocturnal hypoventilation.…”
Section: Introductionmentioning
confidence: 99%